DINAMIKA KOMUNALISME DI INDONESIA DAN KEBIJAKAN PUBLIK - Agustinus Pratisto Trinarso (Arete, 2019)
This paper tries to uncover the dynamics of communalism in Indonesia inthe history of the nation and tries to study it in the realm of philosophical thought.Communalism is based on kinship, regionalism, religion, ethnic identity and oth-ers as a binding and impetus for each individual to prioritize the community overhis own interests as an individual. Communalism is closely related to public policy because communalism always acts on behalf of the public interest in making public policy and communalism demands the obedience of all citizens to carry outpublic policy. Communalism in Indonesia is not a representation of each individ-ual's awareness of their rights and obligations, but a representation of communal /community identity, so that who is the leader and communal figure will determinepublic policy.